2020
DOI: 10.1021/acschembio.9b00939
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Induced Lipid Peroxidation Triggers Ferroptosis and Synergizes with Ferroptosis Inducers

Abstract: Although radiation is widely used to treat cancers, resistance mechanisms often develop and involve activation of DNA repair and inhibition of apoptosis. Therefore, compounds that sensitize cancer cells to radiation via alternative cell death pathways are valuable. We report here that ferroptosis, a form of nonapoptotic cell death driven by lipid peroxidation, is partly responsible for radiation-induced cancer cell death. Moreover, we found that small molecules activating ferroptosis through system xc – inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
250
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 350 publications
(250 citation statements)
references
References 46 publications
0
250
0
Order By: Relevance
“…The expression level of SLC7A11 is higher in either glioblastoma (GBM) patient biopsies or glioma cell lines than in normal brain tissues (44); thus, inhibiting system X − c or GPX4 by ferroptosis inducers enhances the therapeutic effect of radiation in breast cancer, sarcoma, and glioblastoma (40,41,(43)(44)(45). Khorsandi et al showed that the use of gallic acid (GA, a natural polyhydroxy phenolic compound) after pre-irradiation can significantly reduce the survival rate of breast cancer and melanoma cells mainly through inhibition of GPX4 activity without affecting normal cells (42).…”
Section: Ferroptosis In Cancer Radiotherapymentioning
confidence: 99%
“…The expression level of SLC7A11 is higher in either glioblastoma (GBM) patient biopsies or glioma cell lines than in normal brain tissues (44); thus, inhibiting system X − c or GPX4 by ferroptosis inducers enhances the therapeutic effect of radiation in breast cancer, sarcoma, and glioblastoma (40,41,(43)(44)(45). Khorsandi et al showed that the use of gallic acid (GA, a natural polyhydroxy phenolic compound) after pre-irradiation can significantly reduce the survival rate of breast cancer and melanoma cells mainly through inhibition of GPX4 activity without affecting normal cells (42).…”
Section: Ferroptosis In Cancer Radiotherapymentioning
confidence: 99%
“…GBM is an ideal setting for testing this approach because it exhibits profound inter-and intratumoral heterogeneity and is the most common and deadly primary brain malignancy in adults. Surgical resection is part of the standard-of-care, and robust protocols for acute slice culture of human GBM have been established previously [4][5][6] . Furthermore, GBM has been extensively characterized by scRNA-seq providing a detailed baseline for both the transformed populations that co-occur in individual patients and the microenvironment [7][8][9][10][11] .…”
mentioning
confidence: 99%
“…This study exhibits a unique mechanism of ferroptosis protection independent of the GPX4/GSH system. In addition, mitochondrial DNA stress triggers autophagydependent ferroptosis death , and radiationinduced lipid peroxidation also triggers ferroptosis (Ye et al, 2020). These phenomena might be closely related to DNA damage, one of the causes of ferroptosis induced due to lipid peroxidation.…”
Section: Zheng Et Al 2020mentioning
confidence: 99%